2012
DOI: 10.5402/2012/934941
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Becoming a Scholar: A Study of Doctoral Students' Problems and Well-Being

Abstract: Successful studying in Ph. D. education is a complex matter. Although Ph. D. students are a highly select group, some never finish. This paper explores the problems that doctoral candidates face during their doctoral studies as well as students' well-being in relation to their studying engagement. The study is part of a larger research project on doctoral education. Altogether 669 doctoral students from the Faculties of Arts, Medicine, and Behavioural Sciences responded to the survey. Doctoral students' percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
142
4
20

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 152 publications
(177 citation statements)
references
References 49 publications
11
142
4
20
Order By: Relevance
“…A characteristic of generic competences is that they are less domain specific, and hence more easily applied to different working contexts than scientific competences. However previous studies have shown that PhD students often face problems in mastering generic competences (Gilbert et al, 2004;Pyhältö, Toom, Stubb, & Lonka, 2012). PhD students for instance, reported that they suffered from lack of self-regulated learning skills, poor time management, experienced motivational problems and low self-confidence .…”
Section: Introductionmentioning
confidence: 99%
“…A characteristic of generic competences is that they are less domain specific, and hence more easily applied to different working contexts than scientific competences. However previous studies have shown that PhD students often face problems in mastering generic competences (Gilbert et al, 2004;Pyhältö, Toom, Stubb, & Lonka, 2012). PhD students for instance, reported that they suffered from lack of self-regulated learning skills, poor time management, experienced motivational problems and low self-confidence .…”
Section: Introductionmentioning
confidence: 99%
“…Besides, all elements of the general population had equal possibilities to be involved in the research (Kardelis, 2002). It has been emphasised in scientifi c literature that representativeness of a sample is a more important criterion when assessing research validity than the size of a sample (Pyhältö, Toom, Stubb and Lonka, 2012). Representativeness of this research sample is supported by the correspondence of sample characteristics to the data of Lithuanian doctoral students' population (Statistikos departamento internetinė svetainė, 2012(Statistikos departamento internetinė svetainė, -2013.…”
Section: Tyrimo Metodikamentioning
confidence: 95%
“…Supervisor guidance provides the student a salve to counter the identified pitfalls [40]. Implicit in the supervisory process should be a pastoral relationship based on trust and respect [31].…”
Section: Strategies For Increasing Indigenous Doctoral Student Numbersmentioning
confidence: 99%